Effect of drought stress and maternal growth conditions on germination and seedling growth of wild oat (Avena ludoviciana) - A. Nezami; H.R. Khazaie; A.R. Barjasteh (علوم و فناوری بذر ایران)
Because of the importance of the role of maternal environment during seed development on germination of produced seed and seedling establishment an experiment in a randomized complete block design base as a factorial was conducted to evaluate effects of drought stress (0.0, -0.2, -0.4, -0.8 and -1 MPa) on germination and seedling growth characteristics of wild oat seed production under different irrigation regime (100,80 and 60 percentage of water requirement of wheat from stem elongation stage to the end of growth season) in Shahrood Agriculture research center. According to the results, maternal irrigation regime, drought stress and interaction effects between them had significant effect on germination and seedling characteristics of wild oat. The results showed that germination characteristics were decreased significantly with decrease of water potential to -1 MPa. The highest rate and percentage of germination and radicle length in this water potential was related to irrigation regime of 60% water requirement and the least of plumule dry weight was related to irrigation regime of 60 and 80% water requirement. Length and dry weight of plumule decreased more than those of radicle under drought stress conditions and showed greater sensitivity to reduced water potential. Lower dry weight and green area was observed in seedling that germinated at water potential more than -0.4 MPa. The results showed that drought stress during the seed formation caused significant changes in response of wild oat germination under stress condition.